PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 1 BANGKINANG KOTA KABUPATEN KAMPAR - Sari, Arie Maya; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by the teacher's lack of mastery of the learning material because the teacher teaching was not in accordance with the field so that students were not interested and motivated to follow the learning process. Seeing this, the author wants to examine one of the schools in Kampar district to see whether there is an influence of teacher professional competence on student motivation at SMAN 1 Bangkinang Kota, Kampar district. This research is a quantitative descriptive study that became the population in this study, namely class XI students of SMAN 1 Bangkinang kota, Kampar district in the academic year 2021/2022, amounting to 375 people with a sample of 77 respondents determined by proportional random sampling technique. Data collection techniques are observation, questionnaires, documentation, and interviews. The data analysis technique is using a simple linear regression formula assisted by the SPSS version 25 application with the formula Y = a + Bx. With the results of simple linear regression analysis, it is known that the regression equation Y = 45.308 + 0.790X, the results of this equation can be concluded that the constant is 45.308 which means that the consistency value of the student learning motivation variable (Y) is 45.308 while the teacher's professional competence (X) is 0.790 which states that for every 1% addition to the value of a teacher's professional competence (X), the motivation (Y) will increase by 0.790. Based on the results of the research conducted, it can be concluded that there is an influence of teacher professional competence on student learning motivation at SMAN 1 Bangkinang Kota, Kampar district, which is 49%.Key Words: Influence, Professional Competence, Motivation.